Visões da natureza e sua influência na educação ambiental nos livros didáticos e nas escolas - Santos, Thayanna Maria Medeiros (2022)
This work, which falls within the scope of environmental education, had as its main objective to understand how and what the differences on the themes of Environment constitute the object contents of knowledge in public high schools in Campina Grande, Paraíba. More specifically, the objective was: I. To analyze how the Man-nature relationship is manifested in textbooks; II. Identify anthropocentric and biocentric aspects in the approach and insertion of themes related to Environmental Education; III. Understand the discourses of teachers on Environment. The research universe encompassed six state high schools in the city of Campina Grande. The research was guided by the following methodological steps: (1) bibliographic survey, (2) documentary research in schools and (3) phenomenological interview with teachers. The documentary research in schools was carried out through the ecocritical analysis of the contents of high school textbooks in the disciplines of Biology, Geography and Sociology, whose evaluation time frame was the National Textbook Program 2018, totaling 27 books. The phenomenological interviews were carried out in two schools, totaling six participants (two from each subject). The interviews were recorded, transcribed and, after that, analyzed. The books adopted from the National Textbook Program 2018, based on ecocritical analysis, present a language sometimes anthropocentric, sometimes biocentric, but the anthropocentric language prevails in most textbooks. There is a technicist and naive perspective that technology, by itself, will be able to solve socio-environmental problems. Another relevant point is the way in which the Brazilian semiarid region is portrayed in the manuals, conditioning the region exclusively to soil and climate conditions. Regarding phenomenological interviews and teaching participation, it is necessary to remember that in phenomenology there is no “real” in itself, but the “real” as lived by the subject. As for the textbook's contribution to working on environmental issues, the teachers point out three obstacles: time factor, lack of content, lack of contextualization. It was found that most of them carried out environmental training outside the school, which, however, consider having autonomy to work on environmental issues other than those present in the textbooks. Therefore, the thesis was defended that the Anthropocene concept can be a narrative that promotes change, based on the need to replace the binary and dualistic vision that opposes Man-Nature, through the connection of these in the use and application in actions. of education and the environment. Forming citizens who question the technology produced that deteriorates environments, but who also seek to use other technologies in their favor, who recognize that science, technology and research can together build a transformative education, of fair use of the environment, enabling its enjoyment by future generations. Environmental Education can, through these alternatives, bring more significant gains in line with a fully computerized society as we have.